NOVEL HOMOZYGOUS VARIANT OF TBC1 DOMAIN FAMILY MEMBER 8 GENE IN FOUR LIBYAN SIBLINGS WITH AUTISTIC SPECTRUM DISORDER AND INTELLECTUAL DISABILITY WITHOUT EPILEPSY - ZEGLAM, ADEL; ALHMADI, SUAD (Innovare Journal of Medical Sciences, 2021)
Objective: Recent progress in genetic analysis and investigations have enabled researchers to identify potential genetic changes that may play a role in ASD. The number of genes connected with autism is growing. Whole exome sequencing(WES) identified the homozygous TBC1D8 variant. Aim to report for the first time a TBC1D8 missense variant (c.1883G>A, p. (Arg628Gln) in 4 Libyan children (3 homozygous,1 heterozygous) with severe neurodevelopmental phenotypes ASD and intellectual disability ID . Based on the data of HGMD and ClinVar, variants in only a few autosomal recessive intellectual disability ARID genes seem to be reported frequently. Method: Molecular genetic analysis of (WES) was carried out on blood samples from these children. The outcome of the genetic investigations was interpreted within the context of clinical finding, family history, and suspected mode of inheritance. Results: The number of genes associated with autism is increasing. WES identified the TBC1D8 variant. According to the longest isoform (NM_001102426.1),the nomenclature of this variant is c.1883G>A, p. (Arg628Gln) in TBC1D8 which leads to an amino acid exchange. This variant has not previously reported or described in the literature (PubMed, HGMD). Conclusion: we have provided evidence for a connection between TBC1D8 variant and ASD and ID; however, this evidence should be considered preliminary in the context of a single case report and such findings need to be replicated to gain insight in order to determine if ASD and ID are a characteristic of this variant.